Natural Bioactive Compounds against Periodontal Matrix Metalloproteinases: A ChEMBL-LOTUS Chemoinformatics Study - Alexander Mulya; Pham Uyen; Sarah Armalia; Isadora Selestine (Crown: Journal of Dentistry and Health Research, 2025)
Background: Matrix metalloproteinases (MMPs), particularly MMP-8, MMP-9, and MMP-13, contribute to extracellular matrix degradation in periodontitis, but natural-product bioactivity evidence is dispersed across heterogeneous assays. Objective: This study aimed to map IC50 and Ki evidence for natural-product-associated compounds against human MMP-1, MMP-2, MMP-3, MMP-8, MMP-9, and MMP-13 and to identify structurally traceable candidates for orthogonal experimental validation. Methods: Records were extracted from ChEMBL 37 on 5 August 2026 and filtered for positive values with pChEMBL, exact relations, nM units, acceptable validity metadata, no potential-duplicate flag, and direct single-protein assay assignment (confidence score 9). Measurements were summarized by compound-target-endpoint using median pChEMBL. ChEMBL natural-product-flagged candidates were exact-matched by full InChIKey in LOTUS; a study-defined high-support occurrence tier required at least 10 taxa and two reference records. Results: Of 28,002 raw records, 7,451 met the strict criteria. The 153 flagged candidates yielded 42 LOTUS matches and 35 high-support compounds, forming 81 compound-target-endpoint pairs. Isoliquiritigenin showed IC50 values of 10.0 nM for MMP-9 and 14.13 nM for MMP-13, each from one measurement. Caffeic acid showed a median MMP-9 IC50 of 14.62 nM from two assays in one document. No high-support MMP-8 IC50 record was identified; available Ki values were 4.47 micromolar for pyrogallol and 8.71 micromolar for piceatannol. Conclusion: These signals prioritize compounds for orthogonal validation but do not establish periodontal selectivity, safety, or efficacy.